#TITLE_ALTERNATIVE# - MUHENDRA (NIM : 20211034); Pembimbing : Dr. Eng. Maman Budiman, RIFKI
Orthogonal frequency-division multiplexing (OFDM) is a method of digital modulation in which a signal is split into multiple subcarrier channels at different frequencies. This technology is suitable for digital television, and is being considered as a method to obtain high-speed digital data transmission over conventional telephone lines. In this study, the system will be applied to transmit voice in real time. One of the problems in the development of OFDM system is the problem of an increase in data rate by using the Mapping OFDM 64 QAM and the addition of Automatic Gain Control (AGC) to improve the performance of the signal at the receiver. By mapping the system is expected to increase the number of signals operated to be 8 kbps. Based on the results of the simulation and implementation of Automatic Gain Control in OFDM modem in the audio frequency range can be inferred Automatic Gain Control can overcome fluctuations in the received voice signal after passing through the canal, especially in the use of substantial modulation such as 64 QAM. Simulation results show the ability of Automatic Gain Control with this method can effectively improve the performance even of sound on the number of bit errors still show unfavorable results to variations in the frequency offset, the length of FFT and sampling frequency variation.